Second Workshop on Appropriate Sampling Schemes for Protected Endangered and Threatened Species Bycatch (WKPETSAMP2) ... - ICES (ICES Scientific Reports, 2024)
Following the special request from The Directorate-General for Environment (DG ENV), the Second Workshop on appropriate sampling schemes for protected endangered and threatened species bycatch (WKPETSAMP2) was established by ICES. WKPETSAMP2 was tasked to provide input and results to inform ICES advice to DG ENV on ‘appropriate bycatch monitoring systems at Member State level and on regional coordination’. Thereby ICES WKPETSAMP2 was requested to provide recommendations for improvement of monitoring programmes to ensure that collection of data is adequate to assess population level bycatch; in particular, identifying areas, métiers, gears and vessel types where improvements are needed.The most relevant EU legislation and policies were summarized regarding protected species bycatch conservation (i.e. Birds Directive, Habitats Directive etc.) and fisheries monitoring and data collection programmes (i.e. EU Data Collection Framework).Ongoing bycatch monitoring programmes carried out by several Member States ...